Profesionalisme Guru PAI Presepektif Imam Ghazali: Studi Kitab Ayyuhal Walad - Sholahuddin Qoffal; Saiful Arif (Nuris Journal of Education and Islamic Studies, 2026)
Through an analysis of the book Ayyuhal Walad, this study seeks to understand the concept of professionalism among Islamic Religious Education (PAI) teachers from Imam Al-Ghazali's point of view. This study employs a qualitative methodology that incorporates content analysis and library research methods. The research results show that Imam Ghazali implicitly explains the professionalism of PAI teachers through three terms, namely mursyid, wa’idz, and mudzakir. A mursyid is required to have a prophetic attitude and validation of knowledge through a chain of transmission connected to the Prophet. Meanwhile, wa’idz and mudzakir are required to adopt a moderate approach in conveying knowledge and to have the correct methods and intentions in educating. From the exposition, it can be concluded that the professionalism of PAI teachers according to Imam Ghazali in the book Ayyuhal Walad encompasses four important elements contained in these three terms, namely having a prophetic attitude, valid scientific validation, a moderate approach in conveying knowledge, and the use of correct methods and intentions. These findings imply the need for the integration of spiritual, moral, and pedagogical values in forming a comprehensive standard of professionalism for PAI teachers.